CHANGE OF ANTICOAGULANT EFFECT OF RIVAROXABAN DURING A DAY - I. V. Gel’Tser; O. A. Smirnova; O. Yu. Matvienko; O. G. Golovina; L. P. Papayan (Вестник хирургии имени И.И. Грекова)
The article presents an assessment of anticoagulant effect of rivaroxaban in 35 patients with thromboembolic diseases. The results of expressed anticoagulant effect of rivaroxaban were obtained during a day (or more). The data of increase in sensitivity to thrombomodulin indicated about work enchancement of protein C system against the background of rivaroxaban therapy.